Effects of age on the neural correlates of auditory working memory in cochlear implant users - Priyanka Prince; Claude Alain; Joseph Chen; Trung Le; Vincent Lin; Andrew Dimitrijevic (PLoS ONE, 2025)
Following a conversation in a noisy environment is challenging, especially for individuals who received cochlear implants (CIs) to remediate severe-to-profound hearing loss. CI users likely work harder than their normal-hearing counterparts to understand speech in adverse listening conditions. Recruiting cognitive resources can be taxing and may interfere with attentional regulation and working memory processes. Few studies have, however, examined the impact of CIs on the neural correlates of attention and working memory. We used a high-density electroencephalogram to investigate behavioural and neural correlates of auditory attention and working memory in 14 CI users and age-matched normal hearing (NH) controls (age ranges: 21–75). All participants completed an auditory n-back task with zero- and two-back memory load conditions. Behaviourally, CI users were slower in identifying targets during the two-back condition, especially older adults. The sensory-evoked responses were reduced in CI users compared to NH. With increasing memory load, younger CI users and NH controls displayed decreased amplitudes, while older CI users showed no change in amplitude. We also observed reduced frontal theta synchrony and greater alpha/beta desynchrony in CI users where alpha/beta in the left inferior frontal gyrus was related to slower response times in CI users. Attenuated frontotemporal connectivity was also evident compared to NH. These findings suggest that CI users adapt to higher task demands by allocating more attentional resources while encoding and maintaining stimuli in working memory. This pattern of activity potentially indexes a delay in identification and possible neural correlates of cognitive deficits while aging with a CI.